Analisis Fasilitas dan Kepuasan Terhadap Pengembangan Identitas Ikon (Brand Image) Tugu Ketem Remangok Kota Pangkalpinang - Juliansyah, Ari; Muhamad, Nur; Arpandi, Dian; Siregar, Doni Adrian (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
Pangkalpinang City, as the capital of the Bangka Belitung Islands Province, has presented several icons of various nuances. However, of all the icons in Pangkalpinang City, the Ketem Remangok monument icon is not much sought after by the public. So, the problem formulation in this research is as follows: 1) How does the facility (X1) partially influence the brand image (Y) at the Ketem Remangok Monument, Pangkalpinang City? 2) How does satisfaction (X2) partially influence Brand Image (Y) at the Ketem Remangok Monument, Pangkalpinang City? and 3) How do facilities (X1) and satisfaction (X2) influence the Brand Image (Y) simultaneously at the Ketem Remangok Monument, Pangkalpinang City? This research is quantitative, and the sampling technique used in this research is accidental sampling. The sample in this study was 83 respondents who were visitors to the Ketem Remangok Monument, Pangkalpinang City. Data analysis techniques use Validity, Reliability, and Hypothesis Testing (t-Test and F-Test). The variable indicators X1 are public facilities, interior design, exterior design, and cleanliness. The indicator variable X2 is memory, privilege, and pleasure. Meanwhile, the indicators for variable Y are beliefs, impressions, decisions, and actions. In the validity test, all items were declared valid, and the research instrument items were also declared reliable in the reliability test. The result is that there is a positive and significant influence between the facility variable and the brand image variable partially. There is also a positive and significant influence between the satisfaction and partial brand image variables. The F test shows that the facility and satisfaction variables simultaneously have a positive and significant effect on the brand image variable. Thus, it can be concluded that there is a significant favorable influence from the facility and satisfaction variables partially or simultaneously on the development of product identity (Brand Image) at the Ketem Remangok Monument, Pangkalpinang City